Physiological changes of the skin during pregnancy - Vera I. Albanova (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The appearance of skin changes during pregnancy is inevitable and physiologically determined. This period is characterized by hormonal, immunological and metabolic changes and associated physiological changes in the skin. These include pigmentation (linea nigra, melasma, pseudoacanthosis, growth and appearance of pigmented nevi), changes in connective tissue (striae distensae, skin tags), blood vessels (stellate hemangiomas, erythema of the palms, vasodilatation, edema, cutis marmorata) and skin appendages (increased sebaceous and eccrine glands activity, reduced hair loss and increased hair density, onychodystrophy). It is important to inform women about possible changes, to recognize them in time to reduce the impact of their appearance on the health and course of pregnancy, as well as to avoid unnecessary tests and interventions.